Giacomo Leopardi’s Posthumanism. The Operette morali or the Appeal of the Inorganic - Ferri, Sabrina (Rivista Internazionale di Studi Leopardiani, 2023)
In light of recent scholarship on the posthuman, this contribution asks a specific question: how to approach, today, Leopardi’s Operette morali in order to take up the question of his anti-anthropocentric discourse? In order to answer this question, the essay takes as its object Leopardi’s articulation of the tension between organic and inorganic – a distinction which is central to scientific discourses and literary representation between the end of the 18th and the beginning of the 19th centuries. In particular, the essay examines the ways in which, in the Operette morali, Leopardi decenters the human subject through the representation of the inorganic. It shows how Leopardi’s understanding of the the organic/inorganic dyad develops from his evolving materialism and converges with key issues in his philosophical reflection. From a posthumanist perspective, Leopardi’s critique of anthropocentrism takes on new meaning when seen in the context of the opposition between organic and inorganic. It emerges as a practice that questions the centrality of the human through a conceptual redefinition that explores the cognitive and biological limits of human beings.